Learning & Teaching for Interprofessional Practice, Australia (L-TIPP, Aus) : project report : developing interprofessional learning and practice capabilities within the Australian health workforce : a proposal for building capacity within the higher education sector. - Bell, Cheryl; Dunston, Roger; Fitzgerald, Terry; Hawke, Geof; Lee, Alison; Slade, Diana; Matthews, Lynda; Nisbet, Gillian; Pockett, Rosalie; White, Jill; Thistlethwaite, Jill; Lee, Adrian (Australian Learning and Teaching Council, 2009)
The Learning and Teaching for Interprofessional Practice (Australia) (L-TIPP (Aus)) project was initiated in 2007 with the long-term objective of significantly increasing the capacity of the Australian higher education sector to graduate health professionals who have acquired well developed interprofessional learning (IPL) and interprofessional practice (IPP) capabilities. The project adopted a capacity-building model in which it worked interactively and collaboratively with the field to identify the current state of play in interprofessional education, practice and learning both within the academy and in the health system. During the project a widely disseminated consultation document was prepared that scoped existing activity and knowledge in the area and proposed a set of strategies for the next phase of development. The responses to this document enabled the project to refine these strategies and to develop a more specific and targeted proposal called Interprofessional Health Education in Australia: The Way Forward. [Executive summary, ed]